Migrations and education: Warao indigenous children in Roraima - Grajzer, Deborah Esther (2023)
Child migration is a growing contemporary phenomenon. Since 2015, the flow of Venezuelan migrants to Brazil has intensified, especially in the city of Pacaraima, in the state of Roraima. The political and socioeconomic crisis in Venezuela, aggravated by the lack of food and medicine, are the main factors behind this movement. The aim of this article is to understand and analyze the living conditions of Warao children and their access to education. It focuses on the Warao children who migrated to the North of Brazil and were out of school. As a result, the Diocese of Roraima opened a Child Care Center in an urban area in Pacaraima. The school was inaugurated at the beginning of 2019 and received children between the ages of 4 and 11. The space proved to be of great importance for the Warao children, as well as contributing to the process of learning the Portuguese language and literacy. The school's teaching staff is made up of teachers from the Pacaraima municipal education network and Warao educators. The children who attended the school lived in a shelter for the Warao indigenous population, called Janokoida. This experience took place in April 2019, and the data was recorded in a field diary. The analysis seeks to understand the ethnic and cultural diversity inscribed in the daily life of the community and the school. It highlights access to education as a human right that must be guaranteed to all children, regardless of their migration status or ethnicity.